The Effectiveness of Combined Interventions of Infrared, Tens, Massage Release, Scalp Massage, Neck Passive Stretch and Upper Extremity Stretch to Reduce Pain and Increase Functional Activity in Myofascial Trigger Point Syndrome - Kurniawati, Susilo; Rahayu, Umi Budi; Guswiyamto, G (Universitas Muhammadiyah Surakarta, 2022)
Introduction: Long time in computer use and poor work attitude are risk factors for myofascial trigger point syndrome. Occupational overuse can cause adhesions to the myofascial upper trapezius and rhomboid muscles. This can cause local ischemia and tissue hypoxia due to the accumulation of lactic acid, causing pain and decreased functional activity. Case Presentation: A 55-year-old patient with myofascial trigger point syndrome came to the FisioGo clinic Sragen. The patient complained of dizziness and pain in the upper trapezius and rhomboid muscles. Complaints are felt for one week and are very disturbing when on the move or not so lazy to do any activity. Pain is felt to increase when working long hours at the computer. Management and Outcome: After being given a combination of physiotherapy interventions with two visits, the results of pain reduction were obtained using a silent visual analogue scale (VAS) T0:2 cm, T1: 1cm became T2: 0cm, press T0: 5cm, T1: 3cm became T2: 1cm, movement T0: 3cm, T1: 1cm, to T2: 0cm and increased functional activity with neck pain disability index (NPDI) T0: 38%, T1: 20% to T2: 2%. Discussion: Infrared therapeutic effect is vasodilation which can facilitate blood circulation and relaxation. TENS can direct electrical pulses of light to nerves in the area experiencing pain and block pain impulses through large nerve fibers so that the body releases endorphins. Massage release affects the parasympathetic nervous system so that muscle relaxation and blood circulation become smooth in sending oxygen and metabolism to the central nervous system. Scalp massage controls stress which has a positive effect on blood pressure and stabilization of hormone levels because it can reduce sympathetic nerve activation while increasing parasympathetic nerve activation, resulting in a decrease in norepinephrine and cortisol secretion. Stretching can reduce the soft tissue adhesion of the upper trapezius and rhomboid muscles. Conclusion: The combination of infrared, tens, massage release, scalp massage, passive neck stretch and upper extremity stretch with two patient visits can be effective in reducing pain and increasing functional activity in myofascial trigger point syndrome.